Impacts of time delays on distributed algorithms for economic dispatch - Tao Yang; Di Wu; Yannan Sun; Jianming Lian (2015 IEEE Power & Energy Society General Meeting, 2015)
Economic dispatch problem (EDP) is an optimization problem with the objective to minimize the total generation cost subject to the power balance constraint and generator capacity limits. Typically, EDP is solved in a centralized manner, however, recently, several consensus-based algorithms have been proposed to solve EDP in a distributed manner. In these algorithms, it is assumed that information are exchanged through the perfect communication network. However time delays are ubiquitous in the communication network. This paper investigates impacts of communication time delays on a distributed algorithm. This algorithm has been tested by applying time delays to different types of information exchange. Several case studies are carried out to evaluate the effectiveness and performance of the algorithm in the presence of time delays in communication networks. It is found that time delays can negatively affect convergence rate, resulting in the algorithm either converging to an incorrect value or failing to converge altogether.